A consideration of Cleistopetalum and a new combination in Polyalthia (Annonaceae) - Turner, I. M. (Phytotaxa, 2014)
Cleistopetalum is a genus of two species of cauliflorous tree from Borneo and Sumatra. After examining material and photographs it was concluded that Cleistopetalum borneense is a synonym of Polyalthia sinclairiana and Cleistopetalum sumatranum is a synonym of Polyalthia anomala, a species better known by another synonym, Polyalthia clavigera (which is lectotypified here). While Polyalthia in its current delimitation is polyphyletic, it is not immediately obvious how to circumscribe all the clades involved or what generic names should be used. Cleistopetalum will need to be considered along with Monoon, Enicosanthum, Woodiellantha and probably others. The new combination Polyalthia pisocarpa is made for a species from Java previously referred to as P. micrantha, and a neotype is designated.